Florida's Bats: Brazilian Free-tailed Bat - Holly K. Ober; Terry J. Doonan; Emily H. Evans (EDIS)
The Brazilian free-tailed bat lives throughout Florida and is the state’s most common bat. They are important economically because they consume large quantities of insect pests. This 3-page fact sheet explains how to differentiate Brazilian free-tailed bats from velvety free-tailed bats and Florida bonneted bats. Written by Holly K. Ober, Terry Doonan, and Emily Evans, and published by the UF Department of Wildlife Ecology and Conservation, November 2016.